The Association between Dental Pain and Psychological Symptoms: Evidence from a Population-Based Study in Indonesia - Hariyani, Ninuk; Maulina, Tantry; Nair, Rahul (European Journal of Dentistry, 2023)
Objectives This study aimed to determine the prevalence and distribution of dental pain and its association with psychological symptoms: stress and depression.Materials and Methods The 2014 Indonesia Family Life Survey data were used for the abovementioned purposes. Records of self-reported dental pain and stress as well as the occurrence of depression based on the 10-item Center for Epidemiologic Studies-Depression scale were analyzed. Multivariable ordinal regression models were fitted to test the hypothesized associations between dental pain and each of the psychological symptoms, controlling for age, sex, education, wealth, and religiosity.Results Dental pain prevalence among Indonesian population was approximately 15%. The adjusted odds ratios (ORs) from the ordinal regression models indicated that dental pain was related to the increase of the stress and depression level (OR: 1.31, 95% confidence interval [CI]: 1.14–1.49 and OR: 1.59, 95% CI: 1.41–1.79, respectively). Higher education, higher wealth, and being male are risk factors for stress. However, higher wealth and being male are protective factors for depression. Furthermore, higher religious level was a protective factor for both stress and depression.Conclusion Dental pain was associated with a higher level of stress and a higher score of depression, even after being adjusted with age, sex, education, wealth, and religiosity.
Keywords: dental pain; depression; stress; Indonesia; population-based study; epidemiology